Inclusion of Cephalexin in COVID-19 Treatment Combinations May Prevent Lung Involvement in Mild Infections: A Case Report with Pharmacological Genomics Perspective - Khodavirdipour, Amir (Global Medical Genetics, 2021)
Novel coronavirus disease 2019 (COVID-19) is caused by a nonsegmented positive sense RNA, enveloped RNA virus that belongs to the family of β-coronaviridae. This virus shall cause acute respiratory distress syndrome (ARDS) which consequently leads to breathing difficulty and need to admit to intensive care units (ICUs). The current conventional treatment combination in most of the hospitals in Iran includes azithromycin 500 + naproxen 500 + vitamin C 1,000 + Zinc + vitamin D3 1,000. In this case reports (n = 4), we would like to report significant findings in course of COVID-19 treatment reported to our clinic on August 8 and 9, 2020; patients presented as walk in and were advised house isolation and complete bed rest as there were no signs of lung involvement and their overall condition was stable. By the inclusion of cephalexin 500 in treatment combination, patients who received cephalexin 500 for 5 days along with other medicines did not develop any lung involvement and breathing complications. Cephalexin is the gold standard in upper and lower respiratory tract infections and here also shall play a vital role besides other conventional therapies. Azithromycin is a macrodial antibiotic working via the ABCB1 gene pathway. As of date, there is no clear evidence of pharmacogenomics data in COVID-19 patients. More research needs to be performed in COVID-19 before any sort of pharmacogenomics tests could be advised.
Keywords: COVID-19 treatment; SARS-CoV-2; cephalexin; omeprazole